Hubungan Tingkat Pengetahuan Ibu Hamil dengan Partisipasi dalam Melakukan Imunisasi Tetanus Toksoid di Puskesmas Gondang Kabupaten Sragen - Safitri, Ria, Winarsih Nur A, S.Kep.,Ns.,ETN.,M.Kep (2016)
An elimination program tetanus maternal and neonatal is an effort to improve maternal health in Indonesia. This program can be accomplished one of her with tetanus toxoid immunization coverage is high and evenly. Tetanus toxoid immunization is a process to build up immunity as a prevention against tetanus infection. Achievement of tetanus toxoid immunization is influenced by several factors, including education, awareness, experience and knowledge. In doing maternal tetanus toxoid immunization should get at least 2 injections during pregnancy to protect the baby from being infected with neonatal tetanus. In Indonesia in 2014, neonatal tetanus 84 cases and there are 54 cases with the status of who are not immunized.This study design was descriptive correlation with cross-sectional approach. This study population is pregnant women whose gestational age primigravida two weeks before day forecast born (HPL) with a sample of 32 pregnant women with a sampling technique total sampling. Instrument data collection using a questionnaires and secondary data as well as data analysis was performed using correlation analysis and Somers'd Gamma.The results showed knowledge of pregnant women with the highest distribution is approximately as much as 15 respondents (47%). Participation in tetanus toxoid immunization with the highest distribution is not complete as many as 17 respondents (53%). There is a relationship with the level of knowledge of pregnant women participation in tetanus toxoid immunization in Puskesmas Gondang Sragen, with a value of a correlation coefficient 0,741 (p-value = 0, 001).